Penerapan Media E-Comic Materi Sistem Pencernaan Manusia sebagai Upaya dalam Meningkatkan Hasil Belajar Kelas V SDN Burengan 02 Kediri - Giova Wahyu Cyntya; Fajriana Mufida; Devina Mukti Sari; Wiwit Apriliyanti; Liya Ratnawati; Bagus Amirul Mukmin; Aji Setya Gaya Putra (Jurnal Simki Postgraduate, 2024)
The success of 21st century learning can be assessed from the high enthusiasm of students in participating in the learning process, with one of the main supporting factors being the ability to think creatively and achieving learning outcomes. The use of innovative learning media, such as e-comics, can help convey material in a more interesting and interactive way. This research aims to analyze the improvement in learning outcomes of class V students at SDN Burengan 02 Kediri on the subject of the human digestive system by utilizing e-comic media. The research was conducted using the classroom action research (PTK) method in two cycles involving planning, action implementation, observation and reflection, with a sample size of 28 students. The research results showed that the application of e-comic media succeeded in improving student learning outcomes significantly, with an achievement of 61% in the first cycle in the moderately improved category, and increasing to 89% in the second cycle in the very improved category. This proves that e-comic media is not only effective in improving student learning outcomes, but is also able to arouse interest in learning and facilitate understanding of the material, so it is suitable for use as an alternative learning media in class V elementary school.